Encyclopaedia of international corrosion standards - Fomin, G. S. (Maney, for the Institute of Materials, Minerals and Mining, 2003)
This book is one of a series of reference volumes on international standards in various fields of activity prepared by the Russian National Institute for Standardisation (see the author's summary on p. 7). Although initially intended for the benefit of Russian industry and commerce, the subject matter is, by definition, of international value and deserves wider dissemination. The contents have been thoroughly revised and updated by Dr McIntyre.
Keywords: Corrosion and anti-corrosives -- Testing.; Corrosion and anti-corrosives -- Standards.; elektronické knihy; electronic books